Teologi Hindu Dalam Teks Kena Upanisad - Ni Wayan Mia Restiya Damayanti; I Wayan Redi; I Gusti Made Widya Sena (Jurnal Penelitian Agama Hindu, 2019)
The implementation of people's understanding is still largely on the path of Karma or activities. Therefore, a complete and comprehensive understanding is needed by the people in knowing and understanding the true concept of God. Especially Hindu theology in the Text of Upanisad. The formulation of the problems in this study are (1) how the structure of the text affected by upanisad and (2) how the hindu theology in the text of Kena Upanisad. The theory used to dissect the formulation of the problem in this study is the structural theory according to Teeuw to dissect problems regarding the structure of the Kena Upanisad text and the Hermeunetic Theory according to Gadamer to dissect the problems regarding Hindu Theology in the Kena Upanisad text. This research is a descriptive qualitative text or manuscript study. The primary data source in this study is the text Kena Upanisad. Data collection is done by using literature study and document study techniques. The collected data is then analyzed using description techniques, structural analysis, and text interpretation. The results of data analysis are then presented in the form of a description. The results of this study are Hindu theology contained in the text Kena Upanisad which begins by describing whatever teachings contained in the text Kena Upanisad including the concept of God, namely the concept of Brahman in the text Kena Upanisad, Nirguna Brahman, Saguna Brahman, God is One, and God the Source of Life. The implications of the teachings of Hindu theology in the Kena Upanisad texts in this study include (1) Brahman as Satyam, (2) Brahman as Jnanam, (3) Brahman as Ananta and (4) Brahman as Ananda.